El “Consenso de Washington”: antes y después. El caso de Argentina y Perú en el periodo 1990-2008 - Noejovich Chernoff, Héctor Omar (2010)
This paper intends to show that the problem is not in the model itself but in the mismanagement of the prescribed policies. Despite their different social and economical structures, Argentina and Peru faced similar problems during the same period (1990-2000): a hyperinflation in the beginning and an institutional crisis at the end. After several years of economic recovery, Argentina faced a big political and economic crisis and after blaming to the so-called «neoliberal policy», reverses her policy. Actually Peru has better perspectives and Argentina has a collapse in perspective.